Improved earthen stoves in coastal areas in Bangladesh: Economic, ecological and socio-cultural evaluation - Alam, Nazmul; Chowdhury, Sakila (Pergamon, 2010)
The study evaluated the economic, ecological and socio-cultural achievements of improved earthen stoves that were provided to the beneficiaries under a project to improve decreasing biomass energy utilization. A questionnaire was developed and a random sampling method was employed for selecting the samples from the population. The region has undergone a significant change with the development of shrimp aquaculture in brackish water on former paddy field. As a result the households have become dependent on the wood resources of the Sundarban (77% as their first choice of daily fuel). The fuel collection rate from the Sundarban has increased by 30% since the change to aquaculture, while the use of agricultural residues has declined by a similar amount. The introduction of the improved stove with two cook stations and a chimney resulted in a reduction of fuel use (as wood) to 540 g caput−1 d−1, from the previous usage of 810 g caput−1 d−1 using the traditional stove. Households saved 1.5 kg d−1 of fuel (one third), and reduced the cooking time by 45 min d−1 (about 20%). While 85% of men and 65% of women were the major fuel collectors, the improved stove resulted in a small increase (14 taka) in the women’s contribution to family income as well as a monthly saving on fuel cost of 45 taka. Respondents utilized saved time and money for household means and other economic activities.